Bioactivity effect of Elephantopus scaber Linn. extracts against Spodoptera litura and the soil microbial community - Yuliani, Yuliani (Revista de Ciências Agroveterinárias, 2022)
This study investigates the biopesticidal effects of Elephantopus scaber Linn. extract on mortality of Spodoptera litura, Plutella xylostella, and non-target organisms and investigate the impact on S. litura protein levels and soil microbial community structure. The experiment was performed using a completely randomized design. Methanol extracts from E. scaber leaves, at concentrations of 2%, 4%, 6%, 8%, 10%, and 12%, were tested for bioactivity against the 2nd-instar larva of S. litura, P. xylostella, and earthworms. Mortality rates of the larvae and worms were observed. The collected data were analyzed using analysis of variance (ANOVA), followed by probit and descriptive analysis. The results showed that methanol extracts of E. scaber (12%) influenced the highest mortality rates for both S. litura (93.35%) and P. xylostella (96.65%) with LC50 and LC80 of S. litura was 1.867 and 4.763; for P. xylostella were 4.488 and 7.92, respectively. However, the application of E. scaber biopesticide also influences earthworms’ mortality rate. The 6% E. scaber extract resulted in 60% death of earthworms during a 20-days period. In addition, higher concentrations of E. scaber extracts resulted in lower molecular weights and levels of S. litura proteins. The diversity and density of the soil microbial community also decreased by 6% concentration.